2020
DOI: 10.1177/2324709620941313
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET Versus PSMA-PET: A Patient With Prostate Cancer

Abstract: A 64-year old male presented to the hospital with a 1-week history of stools with bright red blood. Subsequent colonoscopy with a biopsy revealed a low-lying, moderately differentiated, rectal adenocarcinoma. A pelvic magnetic resonance imaging done afterwards showed a possible T3N1 rectal cancer with intact muscularis mucosa and a singular presacral lymph node enlargement. Furthermore, a suspicious peripheral prostatic enlargement and a possible left iliac crest sclerotic bone lesion were incidentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Currently, PSMA-PET/CT has been shown to have greater sensitivity, specificity, and negative likelihood ratio in detecting lymph nodes and distant metastasis compared to conventional imaging like CT and MRI [3][4][5][6][7]. Recent studies also suggest that PSMA-PET/CT may have greater sensitivity in detecting bone metastasis when compared to traditional bone scintigraphy [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PSMA-PET/CT has been shown to have greater sensitivity, specificity, and negative likelihood ratio in detecting lymph nodes and distant metastasis compared to conventional imaging like CT and MRI [3][4][5][6][7]. Recent studies also suggest that PSMA-PET/CT may have greater sensitivity in detecting bone metastasis when compared to traditional bone scintigraphy [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, these imaging modalities are not the standard practices in the detection of PCa due to their limited sensitivities for smaller metastases and broad ranges. Choline-PET/CT was reported to have a sensitivity ranging from 73%-91%, and FDG PET/CT had a broad range of sensitivity of 4.0%-80% [ 1 , 4 ]. NaF-PET/CT detects bone metastasis and has shown to have significantly better sensitivity and specificity than conventional bone scintigraphy [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary Table S1 (in supplement) shows the comparison of CECT, FDG-PET-CT, MRI, and PSMA PET-CT for PC. 54 55 56 57 58 59 60 As shown in Table 1 , PSMA PET-CT is superior to the conventional imaging modalities for the localization of primary lesion, staging, and detection of relapse. Besides, PSMA PET-CT also gives lower radiation exposure when compared to CECT and FDG-PET-CT. Supplementary Table S2 (in supplement) shows the comparison of CECT, FDG-PET-CT, MRI, and 68 Ga- DOTATOC PET-CT for NET.…”
Section: Advantages Of Theranostic Pet Over Conventional Imaging In P...mentioning
confidence: 99%
“…Drug-related changes in PSMA expression intensity have to be incorporated as described earlier. Additionally, PSMA imaging enables the detection of tumor mass and heterogeneity and together with FDG-PET it might enable proper staging and the early recognition of tumor dedifferentiation to a more aggressive stage [108]. However, it has also been shown that neuroendocrine differentiation is not always associated with increased FDG uptake, indicating that decreasing PSMA expression is not generally replaced by rising GLUT levels and subsequent detectability by 18 F-FDG-PET [109].…”
Section: Sequence Of Crpc Development: a Putative Scenario Of Psma Detection And Targetingmentioning
confidence: 99%